2018
DOI: 10.3928/1081597x-20180115-03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Two Marking Methods and the Novel toriCAM Application for Toric Intraocular Lens Alignment

Abstract: The novel toriCAM application is able to significantly improve the accuracy of reference marking for both freehand and slit-lamp methods. [J Refract Surg. 2018;34(3):150-155.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Pallas et al found that the toriCAM application, used in the present study, potentially can significantly reduce reference marking errors, thus potentially improving the accuracy of both marking methods; hence, toriCAM use appears to be of greater benefit to the freehand than the slit-lamp method of marking [23].…”
Section: Discussionmentioning
confidence: 56%
“…Pallas et al found that the toriCAM application, used in the present study, potentially can significantly reduce reference marking errors, thus potentially improving the accuracy of both marking methods; hence, toriCAM use appears to be of greater benefit to the freehand than the slit-lamp method of marking [23].…”
Section: Discussionmentioning
confidence: 56%
“…Pallas et al found that the toriCAM application, used in the present study, potentially can signi cantly reduce reference marking errors, thus potentially improving the accuracy of both marking methods; hence, toriCAM use appears to be of greater bene t to the freehand than the slit-lamp method of marking [23].…”
Section: Discussionmentioning
confidence: 55%
“…is was reduced to 1.28°± 1.34°after use of the application (P < 0.001). e toriCAM application for smartphones could improve the accuracy of preoperative marking methods for toric intraocular lens alignment [9]. Another application (Goniotrans) can aid in postoperative measurement of toric axes with camera-enabled cell phones [10].…”
Section: Discussionmentioning
confidence: 99%